O GRUPO DE ESTUDOS COMO ESPAÇO PROBLEMATIZADOR DA PRÁTICA PEDAGÓGICA PARA UMA ESCOLA INCLUSIVA - Pezzi, Fernanda A. S.; Rigo, Neusete M.; Graff, Patricia; Bianchini, Daiani F. (Salão do Conhecimento, 2013)
Resumo